Serotonergic receptor binding in the brainstem in the Sudden Infant Death Syndrome in a high-risk population - Hannah C. Kinney; Rebecca D. Folkerth; Morgan E. Nelson; Lucy Brink; Felicia L. Trachtenberg; Jyoti Angal; Kevin G. Broadbelt; Theonia K. Boyd; Elsie H. Burger; Jean A. Coldrey; Kevin J. Cummings; Jhodie R. Duncan; et al. (PLoS ONE, 2025)
The Sudden Infant Death Syndrome (SIDS) is a major global health problem, with increased risk among socioeconomically disadvantaged populations. We propose SIDS, or a subset, is due to a defect in the brainstem serotonin system mediating cardiorespiratory integration and arousal. This defect impinges on homeostasis during a critical developmental period in infancy, especially in populations experiencing maternal and infantile stress, resulting in sleep-related sudden death. In the socially disadvantaged cohort of the prospective Safe Passage Study from Cape Town, South Africa, and the Northern Plains of the United States, we tested the hypothesis that: 1) serotonin (5-HT) receptor 1A binding is reduced within the brainstem of SIDS infants compared to controls; and 2) reduced 5-HT1A binding in SIDS is associated with maternal drinking and/or smoking during pregnancy. Using receptor ligand autoradiography for the 5-HT1A receptor, 3H-8-OH-DPAT binding was measured in brainstem nuclei in infants dying of SIDS (n = 14) and controls dying of known causes (n = 10). We found a brainstem serotonin defect in SIDS infants, that is strongly driven by preterm birth, and that likely underlies the pathogenesis of sleep-related sudden death in response to homeostatic stress. The findings replicate studies of US low-to-middle income SIDS cohorts, with key differences related to prematurity, including increased 5-HT1A binding in premature SIDS compared to premature controls. The relationship of the serotonin defect to prenatal smoking and drinking is unclear, owing to the high exposure rates in SIDS cases and controls. SIDS was significantly associated with lack of a phone (proxy for poverty) (p = 0.024) and overcrowded housing (p = 0.047). These data support the concept of a serotonin defect in brainstem nuclei mediating cardiorespiratory control and arousal in SIDS infants. Maternal and/or fetal stress, along with premature birth, may underlie a deflection of normal development of the serotonergic system.